Effective hands-on treatment of a corneal dermoid in a calf - HATATE, K; SASAKI, J; KATAYAMA, M; SEKIGUCHI, S; YAMAGISHI, N (Journal of the Hellenic Veterinary Medical Society, 2018)
In the present report, an effective hands-on treatment for a corneal dermoid that extended to the third eyelid, in the left eye of a Japanese Black calf is described. Xylazine sedation and local infiltration anesthesia with 2% lidocaine on the upper and lower eyelids as well as the third eyelid, in combination with topical anesthesia was performed. A Weitlaner retractor allowed immobilizing the patient’s eyeball during surgery, and superficial lamellar keratectomy was performed to surgically excise the mass. A temporary tarsorrhaphy was placed in order to allow the surgical corneal wound to heal as well as to treat keratitis. After an uneventful postoperative recovery, complete cure 70 days post-operatively was achived. This hands-on method represents a practical and effective treatment for ocular dermoids in calves.